Role of seed borne inoculum on karnal bunt infection risks - Sharma, Ramesh Chand; Sharma, Indu (Journal of Cereal Research, 2025)
Field studies on the role of seed borne inoculum of Karnal bunt (KB)and infection risks were carried out at Punjab Agricultural University,Ludhiana during 2003-04 to 2011-12 using the most susceptible wheatvariety, WH 542. The potential of KB infected seeds in causing thedisease in subsequent years was determined by planting seed ofdifferent KB intensities (0.0 -10%) at different sites. The KB continuedto appear up to five years in three of the sites, though in traces insome of the seasons. Weather conditions played a significant rolein the disease development. Nevertheless, the pattern of diseaseoccurrence was often independent of different KB intensities due tolateral movement of infective propagules across the plots. Occurrenceof infection may have depended more on wind direction, randommovement and chance landing of sporidia. Another study conductedfrom 2005-06 to 2007- 08 showed that disease occurred up to 100 m fromthe primary inoculum centre. In third experiment the disease incidencewas observed to be comparatively higher when the bunted grains werepowdered and applied at the soil surface than when used as wholegrains beneath the soil. Even a single powdered infected grain, wascapable of causing considerable infection around 10 m radius. Thefourth and fifth experiments (2006-07 to 2007-08), respectively, carriedout to ascertain the viability of sporidia in relation to nutritionalcomponent and field exposure showed that sporidia maintained theirviability, respectively, for 21, 18 and 9 days in January, February andMarch under field conditions and also on soil extract and leaf washingagar up to 4th sub-culturing indicating their potential to survive andtravel long distances.